Reflections based on Psychology about the effects of COVID-19 pandemic on child development - LINHARES, Maria Beatriz Martins (2023)
Unquestionably, the COVID-19 pandemic threatens the physical and mental health of the population nowadays. In despite of the children are less contaminated in the symptomatic and severe way, these children could be more impacted in the psychological development, as they are a vulnerable population. The present paper addresses the conceptual aspects of Chaos Theory in development and toxic stress, associated with the concepts of self-regulation and coping of stress, aiming to support reflections, from the psychological point of view, about the potential effects of the condition of adversity arising from the pandemic on child development and parenting. The theoretical and conceptual framework supports the comprehension of the adaptive and not adaptive coping types facing the potentially traumatic adverse experience nowadays.